2020
DOI: 10.3390/ijms21030982
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Mimicry Proteins Responsive to α-pinene in Bursaphelenchus xylophilus

Abstract: Bursaphelenchus xylophilus is a nematode species that has damaged pine trees worldwide, but its pathogenesis has not been fully characterized. α-pinene helps protect host species during the early B. xylophilus infection and colonization stages. In this study, we identified potential molecular mimicry proteins based on a comparative transcriptomic analysis of B. xylophilus. The expression levels of three genes encoding secreted B. xylophilus proteins were influenced by α-pinene. We cloned one gene encoding a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…We previously reported that Bx-CPI is most similar to a cystatin-like peptidase inhibitor in the herbaceous plant Medicago truncatula [ 18 ]. However, Meng et al (2020) [ 40 ] reported that Bx-CPI is more similar to the CP inhibitor five-like protein of the common sunflower Helianthus annuus (XP_022033148.1), which shares 32.5% identity with this protein, with over 62% query coverage based on a BLAST analysis of the current database. Although the phylogenetic analysis showed that Bx-CPI clustered in the same clade with an unnamed Enterobius vermicularis (Oxyuridae) protein, no other nematode proteins were clustered to the same group [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that Bx-CPI is most similar to a cystatin-like peptidase inhibitor in the herbaceous plant Medicago truncatula [ 18 ]. However, Meng et al (2020) [ 40 ] reported that Bx-CPI is more similar to the CP inhibitor five-like protein of the common sunflower Helianthus annuus (XP_022033148.1), which shares 32.5% identity with this protein, with over 62% query coverage based on a BLAST analysis of the current database. Although the phylogenetic analysis showed that Bx-CPI clustered in the same clade with an unnamed Enterobius vermicularis (Oxyuridae) protein, no other nematode proteins were clustered to the same group [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Bx-TH1, Bx-TH2, and Bx-CPI mimic host plant defense systems [ 18 ]. Although a very high level of similarity in the amino acid sequences between these PWN proteins and plant proteins was not observed, Wang et al [ 39 ] and Meng et al [ 40 ] suggested that the possible role of these PWN proteins is to mimic host pine defense systems based on the result of phylogenetic and structure prediction analyses. Molecular mimicry is among the best-known strategies for host–parasite defense system evasion and host manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we summarize the recent published findings on the biological and pharmacological activities of pinene (Table 1 (Tab. 1) ; References in Table 1: Bouzenna et al, 2017[ 3 ]; Cardoso et al, 2020[ 4 ]; Chen et al, 2015[ 5 ]; de Macêdo et al, 2018[ 6 ]; do Amaral et al, 2020[ 7 ]; Ensaka and Sakamoto, 2020[ 8 ]; Felipe et al, 2019[ 10 ]; Govindarajan et al, 2016[ 11 ]; Hou et al, 2019[ 12 ]; İnce et al, 2018[ 13 ]; Jensen et al, 2020[ 14 ]; Jo et al, 2021[ 15 ]; Karthikeyan et al, 2018[ 17 ], 2019[ 16 ]; Kasuya et al, 2015[ 18 ]; Khoshnazar et al, 2019[ 19 ], 2020[ 20 ]; Kim et al, 2015[ 21 ]; Kovač et al, 2015[ 22 ]; Kusuhara et al, 2019[ 23 ]; Langsi et al, 2020[ 24 ]; Lee et al, 2017[ 25 ]; Li et al, 2016[ 28 ]; Memariani et al, 2017[ 29 ]; Meng et al, 2020[ 30 ]; Min et al, 2020[ 32 ]; Moreira et al, 2016[ 33 ]; Nóbrega et al, 2020[ 34 ]; Pajaro-Castro et al, 2017[ 35 ]; Pinheiro et al, 2015[ 36 ]; Porres-Martínez et al, 2016[ 37 ]; Rodrigues et al, 2015[ 39 ]; Šimunović et al, 2020[ 41 ]; Ueno et al, 2019[ 44 ], 2020[ 43 ]; Wang et al, 2019[ 46 ]; Xu et al, 2018[ 47 ]; Yang et al, 2016[ 48 ]; Zamyad et al, 2019[ 50 ]; Zhang et al, 2015[ 52 ], 202[ 51 ]0; Zhao et al, 2018[ 53 ]).…”
mentioning
confidence: 99%